Reducing prejudice and discrimination - Oskamp, Stuart (Mahwah : Lawrence Erlbaum Associates, 2000)
Finding ways to reduce prejudice and discrimination is the central issue in attacking racism in our society. Yet this book is almost unique among scientific volumes in its focus on that goal. This combines critical analysis of theories about how to reduce prejudice and discrimination with cutting-edge empirical research conducted in real-world settings as well as in controlled laboratory situations. The authors in this volume focus on a common set of questions about ways to reduce intergroup conflict, prejudice, and stereotyping. Each contributor summarizes their own research as well as others' interprets the conclusions, and suggests implications concerning the practical methods that have been, or could be, used in programs aimed at reducing intergroup conflict. Ideal for teachers, social workers, administrators, managers, and other social practitioners who are concerned about prejudice and discrimination, this book will also serve as a valuable foundation of knowledge in courses that examine this topic.
Multiple paths to reducing prejudice and discrimination / Stuart OskampPart I: Background factors affecting prejudice* An integrated threat theory of prejudice / Walter S. Stephan and Cookie White Stephan* Gender and race discrimination: The interactive nature of disadvantage / Jim Sidanius and Rosemary C. Veniegas* Social contextual strategies for reducing racial discrimination / Marylee C. TaylorPart II: Psychological research on reducing prejudice* Does intergroup contact reduce prejudice: Recent meta-analytic findings / Thomas F. Pettigrew and Linda R. Tropp* Interdependence and the reduction of prejudice / Susan T. Fiske* Reducing contemporary prejudice: Combating explicit and implicit bias at the individual and intergroup level / John F. Dovidio, Kerry Kawakami and Samuel L. Gaertner* Reducing prejudice through cross-categorization: Effects of multiple social identities / Marilynn B. Brewer* Breaking the prejudice habit: Progress and obstaclesPart III: Applications in social settings* Reducing prejudice: The target's perspective / Brenda Major, Wendy J. Quinton, Shannon K. McCoy and Toni Schmader* The three Cs of reducing prejudice and discrimination / David W. Johnson and Roger T. Johnson* Interventions to reduce prejudice and discrimination in children and adolescents / Frances E. Aboud and Sheri R. Levy* Moderators and mediators of prejudice reduction in multicultural education / Michele A. Wittig and Ludwin Molina* Promising practices in reducing prejudice: A report from the President's Initiative on Race / Stuart Oskamp and James M. Jones
Keywords: predrasude - kongresi; diskriminacija - kongresi